2016
DOI: 10.1016/j.bjm.2015.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavone formononetin from red propolis acts as a fungicide against Candida sp

Abstract: A bioassay-guided fractionation of two samples of Brazilian red propolis (from Igarassu, PE, Brazil, hereinafter propolis 1 and 2) was conducted in order to determine the components responsible for its antimicrobial activity, especially against Candida spp. Samples of both the crude powdered resin and the crude ethanolic extract of propolis from both locations inhibited the growth of all 12 tested Candida strains, with a minimum inhibitory concentration of 256 μg/mL. The hexane, acetate and methanol fractions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 18 publications
1
50
0
6
Order By: Relevance
“…Since isoflavones, one of the four compounds it contained can be used as a natural replacement of estrogen, it is popular for its function to alleviate climateric symptoms in older women. Formononetin (7-Hydroxy-4′-methoxyisoflavone, C 16 H 12 O 4 , CAS: 485-72-3, MW: 268.3), one of the major substance in Red clover, has become a focus of study due to its various pharmacological and biological activities, such as anti-tumor [3], anti-oxidant [4], anti-bacterial [5], anti-inflammatory [6], anti-atherosclerosis [7], and anti-osteoporosis [8]. Therefore, it is widely used as an additive in the food and pharmaceutical industries.…”
Section: Introductionmentioning
confidence: 99%
“…Since isoflavones, one of the four compounds it contained can be used as a natural replacement of estrogen, it is popular for its function to alleviate climateric symptoms in older women. Formononetin (7-Hydroxy-4′-methoxyisoflavone, C 16 H 12 O 4 , CAS: 485-72-3, MW: 268.3), one of the major substance in Red clover, has become a focus of study due to its various pharmacological and biological activities, such as anti-tumor [3], anti-oxidant [4], anti-bacterial [5], anti-inflammatory [6], anti-atherosclerosis [7], and anti-osteoporosis [8]. Therefore, it is widely used as an additive in the food and pharmaceutical industries.…”
Section: Introductionmentioning
confidence: 99%
“…HCA (hierarchical cluster analysis) and PLSDA (partial least squares discriminant analysis) were not able to classify the samples based on the chemical markers used. The analysis of vitamins confirmed that BP from this region can be a good source of antioxidant vitamins and that it can provide important nutritional information to food researchers and bioactive compounds for consumers 19 Neves et al [29] The botanical origin of propolis samples is difficult to ascertain on the basis of palynological analysis only, and a more definitive confirmation depends on analysis comparing the chemical profile of the samples with the chemical profile of resins and extracts from the plants found in close vicinity of the bee's hives. It should be stressed that red propolis has been suggested to be the only propolis type derived from a plant from the Leguminosae family (D. ecastaphyllum), rich in isoflavones such as genistein and formononetin.…”
Section: N°bibliographic Referencementioning
confidence: 80%
“…Neves et al (2016) studied the crude ethanolic extract of this substance in comparison to its fractionated derivatives in Candida albicans and Candida tropicallis species. The authors concluded that formononetin is an important compound for the antifungal activity demonstrated by red propolis.…”
Section: Pharmacological Actionmentioning
confidence: 99%